Association Between Obesity and Post-stroke Anxiety in Patients With Acute Ischemic Stroke - Zhu, Bei-Lei; Hu, Ai-Yi; Huang, Gui-Qian; Qiu, Hui-Hua; Hong, Xian-Chai; Hu, Ping-Lang; Yuan, Cheng-Xiang; Ruan, Yi-Ting; Yang, Bo; He, Jin-Cai (Frontiers in Nutrition, 2021)
Post-stroke anxiety (PSA) is a serious psychosomatic comorbidity among stroke patients, but whether obesity could be positively associated with PSA is currently unknown. The purpose of this study was to investigate the potential association between obesity and subsequent anxiety risk in stroke patients. A total of 441 patients with acute ischemic stroke (AIS) onset were consecutively recruited within 7 days, and PSA was evaluated by using 17-item Hamilton anxiety Rating Scale at the end of one-month follow-up. Odds ratio (OR) with 95% confidence interval (CI) was estimated for the incidental PSA by using a logistic regression analysis. The incidence of PSA was 25.85% at the end of one-month follow-up, with a significant difference between patients with and without abdominal obesity. RFM and RFM were significantly associated with elevated risk of PSA, and the crude ORs were 1.04 and 1.93, respectively. Even after adjustment for obesity-related risk factors and PSA-related clinical measurements, the association remained to be pronounced with abdominal obesity. Abdominal obesity is independently associated with the PSA, which is able to help predict PSA risk in clinical practice. Further prospective clinical studies with a long follow-up duration are warranted to verify this finding.